PEARL S. BUCK’S LITERARY ENVIRONMENT AND IDEAS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Pearl S. Buck was a major literary figure of the 20th century, and her works gave us a glimpse into the cultural and social realities of China. What's interesting is that she was a cross-cultural writer, and through her fiction, we can see the roles of women in traditional Chinese society. This study looks at the literary environment that shaped Pearl Buck's writing and the main ideas in her works. Growing up in China as the daughter of American missionaries had a big impact on her worldview and creativity. Her novels explored themes like family values, women's roles, poverty, social inequality, and understanding between different cultures. One of her most famous novels, The Good Earth, tells the story of Chinese peasants and their deep connection to the land. This novel was a huge bestseller in the US and appealed to readers worldwide who wanted to learn more about China. The Japanese, in particular, were fascinated by stories about Chinese farmers. Even today, stories about Buck's life and works are still featured in the Japanese press - by the end of 2022, Japan's top three newspapers had published 568 articles about her. This study also examines how Buck used literature to build bridges between Eastern and Western cultures. Her realistic writing style, humanistic ideas, and social commentary made her a significant voice in world literature. By exploring her works, we can gain a deeper understanding of the cultural and social issues that shaped her writing. Buck's writing continues to be relevant today, offering insights into the complexities of human experience and the importance of cross-cultural understanding.